The Strategy for Development of Bontang City Tourist Attractions Using 4A Analysis - Fareis Althalets; Muhammad Tommy Fimi Putra; Muhammad Fikry Aransyah; Sartika Sartika (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Beras Basah Island and Mangrove Berbas Beach are objects and tourism attractions (ODTW). There are also tourist destinations that have a variety of tourism potential. Currently, the development of the two areas is still not optimal, constrained by internal and external factors regarding the components of attraction, accessibility, amenities, and ancillary (component analysis 4A). The 4A analysis component has not been managed optimally by the manager. Analyzing internal and external factors with a SWOT analysis tool followed by a 4A analysis can help the object and tourism attraction (ODTW) of Beras Basah Island and Mangrove Berbas Beach to develop more by utilizing the existing tourism potentially. This research is a descriptive analysis through a case study; this study aims to determine the Strategy of developing ODTW in Bontang City to increase the tourism sector's economic value. Based on the SWOT analysis results, alternative strategic options for developing ODTW are holding cultural events, using all promotional media, and utilizing tourist sites. It is recommended several things such as managing the location of the residents' business to be neater, completing tourist safety infrastructure, and maximizing the participation of Kelompok Sadar Wiata (POKDARWIS) in tourism activities.